2019
DOI: 10.3389/fneur.2019.00712
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Neuropsychiatric and Cognitive Characterization of Former Professional Football Players: Implications for Neurorehabilitation

Abstract: Objectives: To identify novel targets for neurorehabilitation of people with a remote history of multiple concussions by: (1) comprehensively characterizing neuropsychiatric and cognitive functioning in former professional football players, with a focus on executive functions; (2) distinguishing concussion-related findings from pre-morbid/cohort characteristics of professional football players; and, (3) exploring the relationship between executive functions and neuropsychiatric symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
2
13
1
Order By: Relevance
“…In the present study, a greater lifetime history of concussions and a greater history of exposure to elite-level collision sports were not associated with current symptoms of depression. This study is inconsistent with survey studies of former elite and professional athletes that have shown an association between a greater number of prior concussions and current symptoms of depression ( 17 22 ). Those studies were conducted prior to the greatly increased awareness of, and sensitivity to, concussions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, a greater lifetime history of concussions and a greater history of exposure to elite-level collision sports were not associated with current symptoms of depression. This study is inconsistent with survey studies of former elite and professional athletes that have shown an association between a greater number of prior concussions and current symptoms of depression ( 17 22 ). Those studies were conducted prior to the greatly increased awareness of, and sensitivity to, concussions.…”
Section: Discussioncontrasting
confidence: 99%
“…Researchers have reported that correlates of depression and psychological distress in retired elite and professional athletes include retirement due to injury ( 8 ), greater athletic identity ( 8 ), a higher level of career dissatisfaction ( 11 , 119 ), current adverse life events ( 11 , 12 , 119 ), chronic pain ( 2 , 3 , 66 , 75 ), osteoarthritis ( 116 ), and lifetime history of prior concussions ( 17 22 ). In the present study, neither lifetime history of concussions nor contact sport exposure were meaningfully related to depression in retired elite level rugby league players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in competitive sports, it is necessary to consider other factors, such as the stressful effects of competition and injury potential, among other factors that could influence the behaviour of serum BDNF level. Some cognitive (e.g., anger expression and mental fatigue) and behavioural (e.g., coping skills, competitive anxiety, and mental toughness) characteristics of football players [22,23] could also influence changes in serum BDNF level [24]. The available evidence indicates that exercise is an effective strategy for enhancing BDNF activity, with promising preliminary evidence in high-intensity exercise [1]; however, there is a lack of data available regarding football playing.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of cognitive alterations in RHT, emphasis has been placed on the processes that have shown sensitivity to indicate alterations in athletes, such is the case of working memory, decision-making, planning, inhibition, and reaction times 14,15 . In this sense, the use of computerized tests represents an advantage in the study of repeated blows to the head, since it allows the randomized presentation of the stimuli to avoid the learning effect of a pencil and paper test and the measurement of times reaction rate as a measure of processing speed 16 .…”
Section: Introductionmentioning
confidence: 99%